A catalogue of ichneumonidae ( hymenoptera: inchneumonidae) from Malaysia - Norhafiza , A.F; Idris , A.B (Pusat Sistematik Serangga ,UKM, 2011)
A catalogue of ichneumoninae (hymenoptera:inchneumoninae) from Malaysia which listing 34 species under 10 tribes (Alomyini(=phaeogini), compsophorini,goedartiini, heresiarchini,ichneumonini,ischnojoppini,joppocryptini,listrodromini oedicephalini platylabini and 27 genera are presentes. The tribe heresiarchini has the greatest number of species (12) folled by ichneumonini with 6 species. Imeria is the largest genus which contains 3 species recorded from Malaysia. Type specimens of all species recorded in Malaysia was deposited in various museums or depositories around the world.